2006
DOI: 10.2533/000942906777674859
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic Dithienylethene- Phenanthroline Ligands and their Corresponding Ru(II) Complexes

Abstract: Dithienylethene-phenanthroline ligands as new photochromic systems are described. The photochemical and photophysical properties are strongly influenced by the substituents on the thiophene moiety. The photochromic properties are lost, if one or two methyl groups in position 2 and/or 2' of the target molecules (2o, 3o, 4o) are replaced by isopropyl groups. Replacement of a methyl group by a phenyl group in position 5 and/or 5' shifts the absorption maxima from 514 nm to 575 nm for the free ligand (1c, 2c) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…These results are in line with previously reported absorption properties of 5,6‐bis‐thiophene‐phenanthrolines, accessible via Suzuki‐coupling reactions (L1–4) which have been performed in benzene and acetonitrile, respectively (Table and Scheme ), , ,…”
Section: Resultssupporting
confidence: 92%
“…These results are in line with previously reported absorption properties of 5,6‐bis‐thiophene‐phenanthrolines, accessible via Suzuki‐coupling reactions (L1–4) which have been performed in benzene and acetonitrile, respectively (Table and Scheme ), , ,…”
Section: Resultssupporting
confidence: 92%
“…Phenanthroline is an intriguing compound as fluorescence ligand because its nitrogen atoms in 1 and 10 positions can coordinate with transition metals. Yam and coworkers developed a series of photochromic 5,6‐dithienyl‐1,10‐phenanthroline ligands, which could be coordinated with different metal centers to tune the photochromism with a wide variety of different metal complexes . In addition, the phenanthroline can be modified to form imidazo [4,5‐ f ] [1,10] phenanthroline compounds, in which the NH group in imidazole ring is able to act as fluorimetric sensor for anions .…”
Section: Introductionmentioning
confidence: 99%
“…Yam and coworkers developed a series of photochromic 5,6-dithienyl-1,10-phenanthroline ligands, [37] which could be coordinated with different metal centers to tune the photochromism with a wide variety of different metal complexes. [38][39][40][41] In addition, the phenanthroline can be modified to form imidazo [4,5-f] [1,10] phenanthroline compounds, in which the NH group in imidazole ring is able to act as fluorimetric sensor for anions. [42] For instance, Wang et al reported a Eu(III) complex containing imidazo [4,5-f] [1,10] phenanthroline, in which the addition of F -, HSO 4 -, and AcOcaused significant changes in the absorption and emission spectra.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the molecule undergoes a photocyclization reaction if it is orientated in an anti-parallel array and if the distance between two reactive carbon atoms on the aryl moiety is within 0.42 nm [10]. The photochromic reactivity depends on several factors, such as conformation of the open-ring isomer, the categories of heteroaryl moieties, electron donor/acceptor substituents, and conjugation length of the heteroaryl groups [11][12][13][14][15]. Particularly, the categories of heteroaryl moieties and substituents on the reactive position greatly influence the photoreactivity.…”
Section: Introductionmentioning
confidence: 99%